PENYELESAIAN UTANG PIUTANG ANTARA KOPERASI SIMPAN PINJAM DENGAN ANGGOTA KOPERASI PADA MASA PANDEMI COVID-19 (Studi Penelitian di Kampung Lot Bener Kelipah Kecamatan Bener Kelipah Kabupaten Bener Meriah) - ana, Juli; Yulia, Yulia; Afrizal, Teuku Yudi (Fakultas Hukum Universitas Malikussaleh, 2025)
ABSTRACTCooperatives are associations of people who work together guided by the rules in a law mentioned in Article 44 of Law Number 25 of 1992. These rules are based on the idea of kinship, meaning they want to help each other. When people make agreements in a cooperative, they must follow certain legal rules. This research aims to find out and explain the settlement of debts and receivables between the Lentayon Bunge Senye cooperative and cooperative members and the obstacles and efforts made during the Covid-19 pandemic. This research uses empirical juridical legal research. The research results show that settlement of debts and receivables between the Lentayon Bunge Senye cooperative and cooperative members during the pandemic can be achieved through mutual cooperation Member Meetings (RA). This meeting involves the chairman of the cooperative and other relevant stakeholders. After going through tough discussions, an agreement was reached regarding the settlement of these debts, where it was agreed that 50% of the debt amount would be paid. This agreement will be stated in a written agreement signed by all parties involved. The obstacles faced are non-payment of cooperative members' debts due to the large number of unemployed, reduced harvest yields and decreased business turnover due to the impact of the Covid-19 pandemic. Efforts were made by the Lentayon Bunge Senye Cooperative to resolve this problem through deliberation with all cooperative members to reach an agreement to ease the burden on cooperative members by providing payment relief to cooperative members by paying Rp. 150,000,- (Fifty Thousand) per month. The Lentanyon Bunge Senye Cooperative is expected to carry out a comprehensive assessment of the feasibility of the business owned by its cooperative members.